NGUSABA MELAMPUAN AS A REPRESENTATION OF REALITY IN THE SACREDNESS OF BALI AGA TRADITION IN BAYUNG GEDE TRADITIONAL VILLAGE - Ni Ketut Padma Sari, Ni Ketut Jelita Widia Ariani; Suastika, I Nengah; Pradnyantari, Ni Made Mahysa; Apriani, Ni Komang; Putri, Ni Made Dwi Yulia (Ganesha Civic Education Journal, 2025)
This study aims to examine the Ngusaba Melampuan ritual as a cultural heritage of the Bali Aga community in Bayung Gede Traditional Village, Kintamani District, Bangli Regency, which has strong religious and social values and plays a role in maintaining cultural identity. The research used a descriptive qualitative approach through document studies obtained from scientific journals, articles, research reports, and relevant literature. Data analysis followed the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results showed that Ngusaba Melampuan has a symbolic meaning that is closely related to Bali Aga Hindu beliefs, strengthens social solidarity, and becomes a means of inheriting ancestral values. The implementation of the ritual is carried out for generations with strict customary procedures, starting from the preparation stage, the implementation of the ceremony, to the closing, all of which reflect the community's attachment to tradition. In conclusion, Ngusaba Melampuan plays an important role in maintaining the cultural heritage and identity of the Bayung Gede community amidst the challenges of modernization, as well as contributing to socio-humanities studies related to local traditions and cultural sustainability.